Activating cancer communities through an exercise strategy for survivors: an effectiveness-implementation trial - Heinze, Stefan S.; Chiekwe, C. Joy; Christensen, Thomas; Culos-Reed, S. Nicole; Kendall, Stephanie J.; Langley, Jodi E.; McNeely, Margaret L.; Keats, Melanie R.; Grandy, Scott A. (Frontiers in Cancer Control and Society, 2024)
Introduction Strong evidence supports the recommendation that individuals living with or beyond cancer (LWBC) should be physically active and engage in physical exercise to enhance health and improve cancer-related outcomes. Many individuals LWBC are not achieving these benefits, partly due to a lack of resources. To address this, Activating Cancer Communities through an Exercise Strategy for Survivors (ACCESS) was developed to provide exercise programming and investigate exercise strategies and barriers for those LWBC. Methods Using an effectiveness-implementation design, adults LWBC joined ACCESS by healthcare provider or self-referral. A clinical exercise physiologist triaged participants to either a hospital-based site or one of two community-based sites to complete a 12-week, 24-session multimodal individualized exercise program. Physical fitness and multiple patient-reported outcomes were measured pre- and post-intervention. Results Between January 2018 and March 2020, there were 332 referrals. Of these, 122 participants consented and completed the study. Completing ACCESS was associated with improvements in physical fitness and participant-reported outcomes, including general wellbeing, fatigue, negative emotional states, sleep quality, and exercise self-efficacy. The program was well-received by participants and was deemed feasible and acceptable from an implementation perspective. Discussion The ACCESS program demonstrably improved several health outcomes for individuals LWBC. Implementation outcomes have and continue to guide ongoing efforts to improve accessibility to ACCESS and work with the regional health authority and cancer care program to support the adoption of exercise into standard oncology care. Clinical trial registration clinicaltrials.gov, identifier [NCT03599843].